SYMBOLISM IN THE LYRICS OF S. ESENIN (American Journal of Research in Humanities and Social Sciences, 2023)
The role and significance of symbolism in literature are important aspects that help create depth and complexity in works of art. Symbols are concrete objects, actions, or images that represent abstract ideas, concepts, or emotions. They can be used to convey complex notions, create atmosphere, express profound feelings, and aid the reader in exploring various levels of meaning in a work.